STUDENTS’ ATTITUDE TOWARD HERITAGE LANGUAGE - Akhmad Hairul Umam (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
This research investigates the language attitude of university students in South Jakarta toward the heritage language and language maintenance by employing a questionnaire and an interview. The study also tries to find out students’ efforts in maintaining heritage language and difficulties dealing with heritage language maintenance. Based on the research study most of the students have positive attitude that heritage language maintenance is very important. The challenges with heritage language maintenance are caused by many factors such as the environment, parent’s policy, lack of exposure to learn and to practice the heritage language in speaking, listening, and reading. By taking the case study approach, the present study found that students whose parent from mixed culture tend to neglect heritage language. They prefer to use Indonesian language or other foreign languages instead of heritage language